Molecular detection of Escherichia coli from ovine aborted fetuses in Mosul city, Iraq - Aamer Y. Al-Chalaby; Omer K. Alhankawe; Balsam Y. Rasheed (Iraqi Journal of Veterinary Sciences)
Abortion is one of the major problems in sheep farming. It can result in significant financial losses and presents a major risk to public health. Therefore, the study aimed to isolate Escherichia coli as possibly linked to ovine aborted fetuses, confirm the isolates using PCR, identify the virulence genes, and verify the genetic relatedness of local isolates. Between September 2023 and March 2024, a total of fifty swabs were collected from the stomach contents and placenta of twenty-five aborted fetuses. The swabs were cultured on selective media, and the isolates were characterized using biochemical tests and the Vitek2 system. The isolates that targeted the 23SrRNA gene were verified using PCR. Additionally, specialized primers for the uidA and zapA genes were used. The amplified 23SrRNA gene was sequenced and analyzed. The isolation results showed that Escherichia coli was detected in 10% of the specimens. The PCR results for all five isolates were positive for E. coli, with a product size of 232 bp. Furthermore, all isolates possessed the uidA gene 100%. Nevertheless, the zapA gene was present in 40% of the isolates. GenBank accession numbers PQ191249.1 and PQ191250.1 were registered for the 23SrRNA gene. Genetic relatedness shows that the local isolates were closer to Escherichia coli strain W170 and Escherichia coli O157:H7 strain K1516 from China and USA, respectively. According to these results, a small percentage of pregnant ewes with Escherichia coli infection might have an abortion. Consequently, appropriate precautions must be taken to reduce the infection risk.